Mešana ustava (res publica mixta) pri Ciceronu - Sadek, Mitja (Keria (Ljubljana), 2009)
The article discusses the ancient idea of a mixed constitution, with a specialfocus on Ciceroćs use of the theory in De re publica. It argues for interpreting the political ideas of De re publica on the basis of Cicero's political situation at the time of the dialogue. Contrary to the widespread view of De re publica as an expression of pro-Pompeian monarchism, Cicero arguably saw the idea of the mixed constitution as an instrument for restoring the lost balance between the consuls, the senate, and the comitia. The concluding part of the article addresses the controversial thesis of Alois Riklin, who, in discussing the modern reception of the idea of the mixed constitution, suggests that the paradigm of power division, which is the foundation of modern representative democracy, originates from the ancient theory of the mixed constitution.
Keywords: antika; Cicero, Marcus Tullius; mešana ustava; politična filozofija; ustavna zgodovina